Posted by **sarah** on Saturday, May 12, 2007 at 5:11pm.

how do i solve the following equation?

4 - x = 2 - (3 - 2x)

remove ( ) by distributing - sign

4-x=2-3+2x

then add -4 to both sides to get

-x = -4 + 2 -3 + 2x

then

-x = -5 +2x

then add 2x to both sides

x=-5

## Answer This Question

## Related Questions

- Inter. Algebra - I find it curious here: a - b=2 in this case, rationalize by ...
- Algebra - Which of the following describes a correct method for solving the ...
- Pre Algebra - Here is another one I need help with. -5x+20=-60 ( remember it is ...
- maths - i have to make y the subject of this equation: 4t + 7y - 9 = 0 wod it be...
- Math - Add one to a number, then double the sum, and you get 56. how do i solve...
- math - When you are solving inequalities, when does the sign change and when ...
- Algebra - Solve each literal equations for the indicated variable D = C - s/n ( ...
- Pre Cal.--Check my work? - Solve the system of equations: x - y - z = 2; x + 2y...
- MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...
- science - rearrange this equation 2 make x the subect. 6y = 9 - 3x so first i ...

More Related Questions